2015
DOI: 10.4236/jdm.2015.54036
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Body Mass Index, Japan-Defined and IDF-Defined Waist Circumference, Visceral and Subcutaneous Fat Area with Metabolic Parameters in Japanese Patients with Type 2 Diabetes

Abstract: Obesity is included in the definition of metabolic syndrome. However, there are many controversies surrounding the evaluation of obesity such as body mass index (BMI) and waist circumference (WC) in the definition of metabolic syndrome among various populations. To understand precisely how various anthropometric indices of obesity influence metabolic parameters, we studied the correlations of BMI, WC (Japanese criteria), WC (IDF criteria), visceral fat area (VFA), subcutaneous fat area (SFA) and the VFA/SFA ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Our previous study showed a significant and positive association between serum TG levels and the ratio of visceral fat area (VFA) to subcutaneous fat area (SFA) in obese individuals (28). Further, our other previous studies demonstrated a significant and negative correlation between VFA and HDL-C levels and a significant and positive correlation between VFA and TG levels in patients with type 2 diabetes (29,30), supporting a significant influence of visceral fat on diabetic dyslipidemia.…”
Section: A Significant Influence Of Visceral Obesity On Diabetic Dyslmentioning
confidence: 76%
See 1 more Smart Citation
“…Our previous study showed a significant and positive association between serum TG levels and the ratio of visceral fat area (VFA) to subcutaneous fat area (SFA) in obese individuals (28). Further, our other previous studies demonstrated a significant and negative correlation between VFA and HDL-C levels and a significant and positive correlation between VFA and TG levels in patients with type 2 diabetes (29,30), supporting a significant influence of visceral fat on diabetic dyslipidemia.…”
Section: A Significant Influence Of Visceral Obesity On Diabetic Dyslmentioning
confidence: 76%
“…suggesting a significant influence of visceral obesity on VLDL (29,30). In the accumulated analysis of AEX-HPLC studies, VLDL-C clearly showed higher values in the order of type 2 diabetic patients with obesity, type 2 diabetic patients without obesity, and non-diabetic individuals (21), indicating an importance of VLDL in diabetic dyslipidemia.…”
Section: The Characteristics Of Lipoproteins In Patients With Diabetesmentioning
confidence: 94%